Rationale and preclinical efficacy of a novel anti-EMP2 antibody for the treatment of invasive breast cancer - Fu, Maoyong (2014)
Despite significant advances in biology and medicine, the incidence and mortality due to breast cancer worldwide is still unacceptably high. Thus, there is an urgent need to discover new molecular targets. In this article, we show evidence for a novel target in human breast cancer, the tetraspan protein epithelial membrane protein-2 (EMP2). Using tissue tumor arrays, protein expression of EMP2 was measured and found to be minimal in normal mammary tissue, but it was upregulated in 63% of invasive breast cancer tumors and in 73% of triple-negative tumors tested. To test the hypothesis that EMP2 may be a suitable target for therapy, we constructed a fully human immunoglobulin G1 (IgG1) antibody specific for a conserved domain of human and murine EMP2. Treatment of breast cancer cells with the anti-EMP2 IgG1 significantly inhibited EMP2-mediated signaling, blocked FAK/Src signaling, inhibited invasion, and promoted apoptosis in vitro. In both human xenograft and syngeneic metastatic tumor monotherapy models, anti-EMP2 IgG1 retarded tumor growth without detectable systemic toxicity. This antitumor effect was, in part, attributable to a potent antibody-dependent cell-mediated cytotoxicity response as well as direct cytotoxicity induced by the monoclonal antibody. Together, these results identify EMP2 as a novel therapeutic target for invasive breast cancer.